DAS‐II Cognitive Profiles Are Not Diagnostically Meaningful For Autism: A ROC Analysis. Issue 12 (21st July 2020) - Clements, Caitlin C.; Sparding, Timea; Schultz, Robert T.; Yerys, Benjamin E.; Watkins, Marley W.
Abstract : Intelligence assessment is an integral part of a comprehensive autism evaluation. Many past studies have described a cognitive profile of autistic individuals characterized by higher nonverbal than verbal IQ scores. The diagnostic utility of this profile, however, remains unknown. We leveraged receiver operating characteristic methods to determine the sensitivity, specificity, and area under the curve (AUC) of three different IQ profiles in a large sample of children who have an autism spectrum disorder diagnosis ( N = 1, 228, Simons Simplex Collection) who completed the Differential Ability Scales—Second Edition (DAS‐II), School Age compared to the normative sample provided by the DAS‐II publisher ( N = 2, 200). The frequently discussed nonverbal > verbal IQ profile performed near chance at distinguishing ASD from normative individuals (AUC: 0.54, 95% CI [0.52–0.56]), and performed significantly worse for females than males (AUC: females: 0.46 [0.41–0.52]; males: 0.55 [0.53–0.58]). All cognitive profiles showed AUC < 0.56. We conclude that while significant differences between verbal and nonverbal IQ scores exist at the group level, these differences are small in an absolute sense and not meaningful at an individual level. We do not recommend using cognitive profiles to aid in autism diagnostic decision‐making. Lay Summary: Some researchers and clinicians have reported an "autistic cognitive profile" of higher nonverbal intelligence than verbal intelligence. In an analysis of over 1, 000 autistic children, we found that the group's average nonverbal intelligence is usually higher than their verbal intelligence. However, this pattern should not be used by clinicians to make an individual diagnosis of autism because our results show it is not helpful nor accurate.